The Right to a Healthy Environment - Barus, Sonia Ivana; Widiyarti, Diyas (Journal of Contemporary Sociological Issues, 2024)
As a pivotal justice enforcement agency in Indonesia, the State Administrative Court (PTUN) is instrumental in protecting citizens' rights, particularly in cases where administrative decisions by state officials cause harm. This article critically analyzes the implications of this problem construct judge decisions, explicitly focusing on environmental destruction cases. The interpretation of legal provisions plays a decisive role in determining outcomes. However, explaining the background of rationality used by judges is still being debated among scholars. Through an in-depth examination of several judicial decisions, the study identifies significant inconsistencies in interpreting Article 53 Paragraph (1) of the Administrative Court Law, especially concerning the phrase' interests are harmed.' These inconsistencies undermine legal certainty and expose underlying sociological issues, including power imbalances and social inequality. Mainly, that disproportionately hinders vulnerable communities from accessing justice. The analysis suggests that if left unaddressed, these disparities could further erode the principle of equality before the law, a cornerstone of justice, and weaken the foundations of environmental justice in Indonesia. A systematic interpretation is used to develop alternatives to overcome the challenges arising from ecological rights. Based on the inconsistency of Article 53 Paragraph (1) interpretation, this article argues that harmonization with domestic laws and international environmental agreements is the legal foundation. Furthermore, this approach is essential for reinforcing the judiciary's role in upholding citizens' rights, ensuring equitable access to justice, and strengthening Indonesia's legal framework for environmental protection. Keywords: Environment, Inconsistency, Justice, Rights, State Administrative Court